Heterogeneity of PD-L1 Expression in Lung Mixed Adenocarcinomas and Adenosquamous Carcinomas. (March 2020) - Zito Marino, Federica; Rossi, Giulio; Montella, Marco; Botti, Gerardo; De Cecio, Rossella; Morabito, Alessandro; La Manna, Carmine; Ronchi, Andrea; Micheli, Mariacarolina; Salatiello, Giuseppe; Micheli, Pietro; Rocco, Danilo; et al.
Abstract : Immune checkpoint inhibitors against programmed cell death protein 1/programmed death-ligand 1 (PD-L1) have proven to be remarkably effective in non–small cell lung cancer. PD-L1 represents a predictive biomarker in lung cancer, although its heterogenous expression represents an emerging challenge for accurate biomarker-based patient selection. Lung adenocarcinomas (ADCs) show a high rate of intratumor morphologic heterogeneity that may reflect a heterogenous molecular and immunophenotypic profile. The aim of our study was to analyze the expression of PD-L1 in different intratumor subtypes and/or growth patterns in a series of mixed adenocarcinomas (mADCs) and adenosquamous lung carcinomas (AdSqLCs). As many as 73 mADCs and 6 AdSqLCs were selected. Comprehensive histologic subtyping was performed, and PD-L1 expression was assessed by immunohistochemistry assay using different primary antibodies and automated immunostainers. Overall, PD-L1 expression was observed in 37 of 79 cases (39.2%) (31 mADCs and all AdSqLCs). PD-L1 expression was heterogenous in 22 of 37 PD-L1-positive cases (23.2% mADC and 83% AdSqLC). PD-L1 expression was observed more frequently in ADC with solid pattern. Heterogeneity of PD-L1 expression was significantly related to the presence of micropapillary ( P =0.028) and solid ( P =0.017) patterns. All PD-L1-positive cases were epidermal growth factor receptor wild-type, 2 cases harbored concomitantly PD-L1 expression and ALK rearrangement. Our data suggest that PD-L1 expression is quite heterogenous in mADCs and AdSqLCs, partly contributing to explaining the discrepant results between biopsy and surgical resections and discordant clinical effectiveness in regard to PD-L1-positive or negative ADC diagnosed on cytology/small biopsy.